2002
DOI: 10.1037/0096-1523.28.4.798
|View full text |Cite
|
Sign up to set email alerts
|

The siren song of implicit change detection.

Abstract: Although change blindness could suggest that observers represent far less of their visual world than their conscious experience leads them to believe, they could fail to detect changes even if they fully represent all details. Reports of implicit change detection in the absence of awareness are consistent with the notion that observers' representations are more complete than previously thought. However, to provide convincing evidence, studies must separate implicit detection from explicit processes. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
146
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(172 citation statements)
references
References 37 publications
18
146
8
Order By: Relevance
“…by Mitroff et al (2002), it seems that these effects persist even after the correction of potential biases Laloyaux et al, 2006). It therefore seems that a change that observers report as being unaware of can influence subsequent behavior.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…by Mitroff et al (2002), it seems that these effects persist even after the correction of potential biases Laloyaux et al, 2006). It therefore seems that a change that observers report as being unaware of can influence subsequent behavior.…”
Section: Introductionmentioning
confidence: 96%
“…Crucially, in our paradigm, participants were not informed that a change may occur, and we focused data analysis on those participants who had remained unaware of the fact that some stimuli were changing. This is important for previous studies (Angelone et al, 2003;Hollingworth & Henderson, 2002;Mitroff et al, 2004;Scott-Brown et al, 2000;Silverman & Mack, 2006;Simons et al, 2002) have demonstrated that some information both about pre and post-change displays is stored when observers are forewarned that a change may occur This issue is also related to recent debates about implicit change detection (Fernandez-Duque, Grossi, Thornton, & Neville, 2003;, 2003Laloyaux, Destrebecqz, & Cleeremans, 2006;Mitroff, Simons, & Franconeri, 2002;, 2002. For instance, FernandezDuque and presented their subjects with changes of orientation of horizontal and vertical rectangles and showed that, even when subjects reported being unaware of a change, they were nevertheless able to localize the change above chance level.…”
Section: Introductionmentioning
confidence: 99%
“…Such processes might register the presence of a change before conscious perception, either via the possible [27] operation of implicit processes [14,[28][29][30] or via other mechanisms such as 'mindsight' -the ability of some observers to experience a 'gut feeling' as to the presence of a change before they visually identify it [31]. This 'sensing' of a change might constitute a new perceptual mechanism revealed through the use of change blindness (but see [32]).…”
Section: Insights Into Other Visual Processesmentioning
confidence: 99%
“…Signals that are strong enough to pass a threshold for explicit change detection will result in an explicit behavioral response to the change (e.g., "Yes, there was a change"; see Fernandez-Duque & Mitroff, Simons, & Franconeri, 2002). According to signal detection theory, observers set a critical threshold for deciding whether a particular signal is strong enough to result in explicit detection (Green & Swets, 1966).…”
Section: Explicit Response Activationmentioning
confidence: 99%